Integrated analysis of HSP20 genes in the developing flesh of peach: identification, expression profiling, and subcellular localization - Chunhua Zhang; Yanping Zhang; Ziwen Su; Zhijun Shen; Hongfeng Song; Zhixiang Cai; Jianlan Xu; Lei Guo; Yuanyuan Zhang; Shaolei Guo; Meng Sun; Shenge Li; et al. (BMC Plant Biology, 2023)
Abstract Background Plant HSP20s are not only synthesized in response to heat stress but are also involved in plant biotic and abiotic stress resistance, normal metabolism, development, differentiation, survival, ripening, and death. Thus, HSP20 family genes play very important and diverse roles in plants. To our knowledge, HSP20 family genes in peach have not yet been characterized in detail, and little is known about their possible function in the development of red flesh in peach. Results In total, 44 PpHSP20 members were identified in the peach genome in this study. Forty-four PpHSP20s were classified into 10 subfamilies, CI, CII, CIII, CV, CVI, CVII, MII, CP, ER, and Po, containing 18, 2, 2, 10, 5, 1, 1, 2, 1, and 2 proteins, respectively. Among the 44 PpHSP20 genes, 6, 4, 4, 3, 7, 11, 5, and 4 PpHSP20 genes were located on chromosomes 1 to 8, respectively. In particular, approximately 15 PpHSP20 genes were located at both termini or one terminus of each chromosome. A total of 15 tandem PpHSP20 genes were found in the peach genome, which belonged to five tandemly duplicated groups. Overall, among the three cultivars, the number of PpHSP20 genes with higher expression levels in red flesh was greater than that in yellow or white flesh. The expression profiling for most of the PpHSP20 genes in the red-fleshed ‘BJ’ was higher overall at the S3 stage than at the S2, S4-1, and S4-2 stages, with the S3 stage being a very important period of transformation from a white color to the gradual anthocyanin accumulation in the flesh of this cultivar. The subcellular localizations of 16 out of 19 selected PpHSP20 proteins were in accordance with the corresponding subfamily classification and naming. Additionally, to our knowledge, Prupe.3G034800.1 is the first HSP20 found in plants that has the dual targets of both the endoplasmic reticulum and nucleus. Conclusions This study provides a comprehensive understanding of PpHSP20s, lays a foundation for future analyses of the unknown function of PpHSP20 family genes in red-fleshed peach fruit and advances our understanding of plant HSP20 genes.